The relationship between the teachers theoretical orientation to reading and their practices - Yakzan, Lama Anwar (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2001)
The purpose of this study was to survey teachers' theoretical orientations to reading and their endorsement of developmentally appropriate practice (DAP) in Beirut District (Zone I). In addition, the study examined the relationship between reading orientations, endorsement of DAP, and teaching experience The sample consisted of 131 elementary English teachers in public, private non-profit schools, and private schools in Beirut. All subjects were asked to respond to the DeFord Theoretical Orientation to Reading Questionnaire (TORP) to measure their theoretical orientations to reading, and to the Primary Teacher Questionnaire (PTQ), to measure the degree to which they endorse developmentally appropriate practice. Both TORP and PTQ were first piloted. Composite scores, means, standard deviations, total and subtotal scores were obtained for each of the TORP and PTQ Descriptive statistics were computed to determine the teachers' theoretical orientations to reading Correlational analysis was conducted to identify the possible relationship among the variables under study. To examine the effect of the number of years of teaching experience on the teachers' theoretical orientations to reading and their endorsement of developmentally appropriate practice, descriptive statistics were computed and a MANOVA test was run. It was concluded that the phonics orientation was more dominant than the skills and the whole language orientations, and that the whole language orientation was the least prevalent among the teachers' beliefs. Results revealed a high positive correlation between the whole language orientation and the DAP. It was also concluded that experience was negatively correlated with the whole language approach and the DAP Results were described and discussed in terms of the relationship between teachers' orientations and practices.
: Mémoire
Keywords: Enseignement des langues; Les Attitudes et conceptions des enseignants; Teachers attitudes and conceptions; Teaching languages